Individual Differences in Second Language Listening: Examining the Role of Knowledge, Metacognitive Awareness, Memory, and Attention. Issue 1 (8th July 2020) - Wallace, Matthew P.
Abstract: The aim of this study was to examine the direct and indirect effects of domain‐specific knowledge (vocabulary knowledge and topical knowledge) and domain‐general cognitive abilities (metacognitive awareness, memory, and attentional control) on second language listening comprehension. Data were collected from 226 Japanese senior high school EFL students. Data sources included a practice version of the TOEFL Junior Standard test, the Listening Vocabulary Levels Test, the Metacognitive Awareness Listening Questionnaire, memory recall tests, attentional control tests, and a study‐generated questionnaire measuring topical knowledge. Scores from these instruments were examined using structural equation modeling. The results showed that vocabulary knowledge had the strongest total effect on listening performance. Topical knowledge and attentional control also had direct effects. Only metacognitive awareness had an indirect effect on listening comprehension through topical knowledge. The findings indicate that differences in domain‐specific knowledge, particularly vocabulary knowledge, are the most important for predicting listening comprehension. Abstract :